2022
DOI: 10.1002/essoar.10510816.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of the January 2022 Tonga volcanic eruption on the ionospheric dynamo: ICON-MIGHTI and Swarm observations of extreme neutral winds and currents

Abstract: Institional Repository GFZpublic: https://gfzpublic.gfz-potsdam.de/ IntroductionIsolated disturbances such as earthquakes, tsunamis, and solar eclipses, as well as explosions from volcanoes, nuclear detonations, and meteor air bursts can offer discrete tests for models of atmosphere-ionosphere coupling and variability (Aryal et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 4 publications
2
20
1
Order By: Relevance
“…Using ICON thermospheric wind measurements, Harding et al. (2022) and Aa et al. (2022) found that both zonal and meridional winds exhibited strong oscillations as large as ±200 m/s following the passage of volcano‐induced Lamb waves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using ICON thermospheric wind measurements, Harding et al. (2022) and Aa et al. (2022) found that both zonal and meridional winds exhibited strong oscillations as large as ±200 m/s following the passage of volcano‐induced Lamb waves.…”
Section: Discussionmentioning
confidence: 99%
“…The PRE peak intensity could be enhanced by in‐phase superposition of eastward perturbation wind due to AGWs and the background zonal wind (Abdu et al., 2009; Kudeki et al., 2007). Some recent studies showed that this volcanic eruption caused extreme thermospheric zonal winds oscillation with the maximum eastward component reaching 200 m/s together with strong equatorial electrojet following the passage of volcano‐induced Lamb waves (Harding et al., 2022; Le et al., 2022). In comparison, our study of the ICON‐IVM vertical drift measurements clearly demonstrates that the dusktime PRE near epicenter longitude was indeed largely enhanced to 60–120 m/s (Figures 6f, 6i, and 6l) following the volcanic eruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the irregularities are detected during the recovery phase, about 12 hr after the end of the storm's main phase. Therefore, the development of irregularities is not likely to be associated with storm‐induced electric fields (Harding et al., 2022). As Figures 3a–3d reveal, the occurrence and strength of irregularities do not show any correlation with the Kp index.…”
Section: Discussionmentioning
confidence: 99%
“…The Hunga‐Tonga event primarily draws attention from the aeronomy community because of its global impact on the atmosphere. The observations of its footprint worldwide provide an unprecedented opportunity to assess the generation and propagation of various atmospheric waves and their effect on the ionosphere (Aa et al., 2022; Amores et al., 2022; Harding et al., 2022; Lin et al., 2022; Themens et al., 2022; Wright et al., 2022; S. R. Zhang et al., 2022). The total electron content (TEC) measurements from the dense Global Navigation Satellite System (GNSS) network on the ground provide a means to trace near‐ and far‐field atmospheric waves.…”
Section: Introductionmentioning
confidence: 99%